The Importance of Supervised Learning in the Operation of Modern Techniques - Babajanov Boburbek Farhodovich; Ollaberganova Muyassar Davlatboy qizi; Ravshanqulov Abbos Ravshanqul o’g’li; Abdalova Hilola Batirovna (Zien Journals, 2022)
This article discusses the importance of supervised learning and how it is widely used today. In addition, information was provided on the types of Supervised Learning, such as Classification and Regression, and the advantages and disadvantages of this learning. In addition, the importance of this training in the work of modern technologies is explained.
Keywords: Machine Learning; Classification; Regression; predictor